(untitled) (Architecture Image Studies, 2020)
In architectural drawings, human figures are generally requested to express the scale of design space and to illustrate the functions, but many cases demonstrate they are capable of playing cultural roles, indirectly revealing the architects’ ideological positions toward society. By comparing their use in the work of Otto Wagner, Mies van de Rohe, Le Corbusier, and Mansilla and Tuñón, this article analyses their role as visual mediator between representation and reality according to the different graphical techniques and their intertextual potential to connote the representation and the specific figures adopted. In particular, it focuses on the case of the cameo, and the cameo of the architect in particular, to discuss the semantic consequences on the drawing and to frame it into the wider, pictorial typology of the portrait of an architect.